The art of enterprise information architecture : a systems-based approach for unlocking business insight - Godinez, Mario (Upper Saddle River, NJ : IBM Press, Pearson, 2010)
The book highlights the importance of dynamic warehousing, enterprise information architecture from conceptual, logical, component, and operational views. It also shows how to use information architecture principles to integrate and rationalise your IT investments, from cloud computing to information service lifecycle management.
The imperative for a new approach to information architecture -- Introducing enterprise information architecture -- Data domains, information governance, and information security -- Enterprise information architecture : a conceptual and logical view -- Enterprise information architecture : component model -- Enterprise information architecture : operational model -- New delivery models : cloud computing -- Enterprise information integration -- Intelligent utility networks -- Enterprise metadata management -- Master data management -- Information delivery in a Web 2.0 world -- Dynamic warehousing -- New trends in business analytics and optimization.
Includes bibliographical references and index.
uaj 2/12/2013
Loans
Keywords: Information technology -- Management; Management information systems; Business enterprises -- Computer networks -- Security measures; Information technology -- Security measures